Republic of Armenia : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2006)
The Armenian government adopted the Poverty Reduction Strategy Paper (PRSP), and the first years of the PRSP implementation have evidently resulted in the significant reduction of both poverty and extreme poverty. The main focus has been sustainable economic growth, institutional reforms, and poverty reduction targeted policy in individual spheres. The annual budget is fully based on the PRSP ideology and was programmed accepting the priorities set up in the PRSP. The government considers the medium-term expenditure framework as a key mechanism to overcome poverty.